Yukon First Nation use of Copper for End-Blades on Hunting Arrows - Thomas, Christian Daniel; Hare, P. Gregory; Reuther, Joshua D.; Rogers, Jason S.; Cooper, H. Kory; Dixon, E. James (Journal of Glacial Archaeology, 2020)
Copper metallurgy and bow and arrow technology are widely considered hallmark traits of the Late Prehistoric Period in the northwest of North America (Yukon and Alaska). In recent years, a number of osseous arrow points have been recovered from melting alpine ice patches in the northwest, some with evidence of copper utilization. This article reports on the construction and radiocarbon dating of three osseous arrowheads recovered from Yukon-Alaska ice patches and documents the use of handheld energy-dispersive x-ray florescence (EDXRF) technology to discriminate native copper implements, as well as detect absorbed copper residues from other osseous points. We also reference several other bladed arrow points discovered at ice patches in Yukon and neighboring Alaska to develop a tentative timeline for the use of copper end-blades with osseous arrow points in the northwest.